A pure familial 6q15q21 split duplication associated with obesity and transmitted with partial reduction. (21st April 2015) - Landais, Emilie; Leroy, Camille; Kleinfinger, Pascale; Brunet, Stéphanie; Koubi, Valérie; Pietrement, Christine; Poli‐Mérol, Marie‐Laurence; Fiquet, Caroline; Souchon, Pierre‐François; Beri, Mylène; Jonveaux, Philippe; Garnotel, Roselyne; et al.
Abstract : Familial transmission of chromosome 6 duplications is rare. We report on the first observation of a maternally‐inherited pure segmental 6q duplication split into two segments, 6q15q16.3 and 6q16.3q21, and associated with obesity. Obesity has previously been correlated to chromosome 6 q‐arm deletion but has not yet been assessed in duplications. The aim of this study was to characterize the structure of these intrachromosomal insertional translocations by classic cytogenetic banding, array‐CGH, FISH, M‐banding and genotyping using microsatellites and SNP array analysis, in a mother and four offspring. The duplicated 6q segments, 9.75 Mb (dup 1) and 7.05 Mb (dup 2) in size in the mother, were inserted distally into two distinct chromosome 6q regions. They were transmitted to four offspring. A son and a daughter inherited the two unbalanced insertions and displayed, like the mother, an abnormal phenotype with facial dysmorphism, intellectual disability, and morbid obesity. Curiously, two daughters with a normal phenotype inherited only the smaller segment, 6q16.3q21. The abnormal phenotype was associated with the larger proximal 6q15q16.3 duplication. We hypothesize a mechanism for this exceptional phenomenon of recurrent reduction and transmission of the duplication during meiosis in a family. We expect the interpretation of our findings to be useful for genetic counseling and for understanding the mechanisms underlying these large segmental 6q duplications and their evolution. © 2015 Wiley Periodicals, Inc.